A milk protein gene promoter directs the expression of human tissue plasminogen activator cDNA to the mammary gland in transgenic mice. - Pittius, C W (1988)
Whey acidic protein (WAP) is a major whey protein in mouse milk. Its gene is expressed in the lactating mammary gland and is inducible by steroid and peptide hormones. A series of transgenic mice containing a hybrid gene in which human tissue plasminogen activator (tPA) cDNA is under the control of the murine WAP gene promoter had previously been generated. In this study, 21 tissues from lactating and virgin transgenic female mice containing the WAP-tPA hybrid gene were screened for the distribution of murine WAP and human tPA transcripts. Like the endogenous WAP RNA, WAP-tPA RNA was expressed predominantly in mammary gland tissue and appeared to be inducible by lactation. Whereas WAP transcripts were not detected in 22 tissues of virgin mice, low levels of WAP-tPA RNA, which were not modulated during lactation, were found in tongue, kidney, and sublingual gland. These studies demonstrate that the WAP gene promoter can target the expression of a transgene to the mammary gland and that this expression is inducible during lactation.